IMPLEMENTASI LKS EKSPERIMEN PADA KONSEP LARUTAN ELEKTROLIT DAN NON ELEKTROLIT TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 8 AMBON - Lisa V Paays; Yeslia Utubira; Y T Filindity (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2011)
The research to identify student’s study result through the implementation of student worksheet experiment to electrolit and non electrolit concept had been done. This research was descriptively by using the student’s grade X2 and X3 as the research subjets. Data of student’s study result was obtained by formative test, afective assessment sheet, and psychomotor assessment sheet. Based on analysis result, it was obtained that 20 student’s (44,44%) got very good qualification and 25 student’s (55,55%) got good qualification. Thus, it can be can cluded that the implementation of student worksheet experiment to electrolit and non electrolit concept could motivate the student’s in study process where the result was obtained for all student (100%) had achieved the minimum criteria for completeness (KKM) in SMA Negeri 8 Ambon